ECOLOGICAL SIGNIFICANCE AND HABITAT DISTRIBUTION OF EUPHORBIACEAE FAMILY IN POINT CALIMERE WILDLIFE SANCTUARY, TAMIL NADU - M, Padma Sorna Subramanian; A, Saravana Ganthi; K, Subramonian (International Journal of Allied Sciences (IJAS), 2022)
The Euphorbiaceae family is comprised of over 8000 species of flowering plants distributed worldwide, including woody trees, shrubs, cacti-like shrubs, and herbs. The family has great economic importance and has been utilized for medicinal purposes by local populations in various countries. The aim of this study was to document and enumerate Euphorbian plants in Point Calimere Wildlife and Bird Sanctuary in Tamil Nadu, India. A total of 15 genera and 29 species were recorded, with 24 species currently used in disease treatment. The study area was found to have 15 herbs, 12 shrubs, and 2 trees, and the common xerophytic species included Euphorbia antiquorum and Securinega leucopyrus. This study provides a key to identifying different genera in the Euphorbiaceae family. The study also reveals the loss of native plants due to the massive spreading of Prosopis chilensis and its impact on the tropical dry evergreen forest habitat in the area. The present study contributes to increased knowledge of biodiversity in a protected area that has important biological richness.